Suppression of Fusarium oxysporum f. sp. gladioli populations in soil by application of Trichoderma virens and in vitro approaches for understanding biological control mechanisms - and U.S. SINGH, P.K. MISHRA*, A.N. MUKHOPADHYAY (Indian Phytopathology, 2004)
An isolate of Trichoderma virens was antagonistic to Fusarium oxysporum f. sp. gladioli, a pathogen of gladiolus corm rot and wilt. The proliferation and population density of F. oxysporum f. sp. gladioli in the soil was significantly reduced after the incorporation of T. virens. After three weeks, the log colony forming units of F. oxysporum f. sp. gladioli was significantly reduced in T. virens incorporated soil (5.2 log CFU/gm soil) in comparison with control, where it was 6.1 log CFUs. In vitro studies revealed that mechanisms operative in antagonism were competition and antibiosis. A negatively exponential relationship was observed between the amount of T. virens culture filtrate and the growth of F. oxysporum f. sp. gladioli, whereas, there was positive exponential relationships between T. virens culture filtrate and F. oxysporum f. sp. gladioli growth.